1990
DOI: 10.1128/iai.58.9.3116-3121.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression in Escherichia coli of a protective antigen of Erysipelothrix rhusiopathiae

Abstract: Erysipelothrix rhusiopathiae is a primary pathogen of swine and turkeys and sporadic cause of disease in a variety of other hosts, including humans. A genomic library of the highly virulent strain of E. rhusiopathiae E1-6P was constructed in the expression-cloning vector Xgtll and screened with serum from a pig convalescent from an E. rhusiopathiae experimental infection. Immunoreactive clones were screened for their ability to protectively immunized mice. Two clones, AgtlllersA and Agtll/ersB, were obtained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Furthermore, they suggested that the antibody to the 64 kDa protein was important in the protection of mice against E. rhusiopathiae infection. GALÀ N and TIMONEY (1990) suggested that the antibody to the protective antigen expressed in Escherichia coli reacted strongly with the 66, 64 and 43 kDa proteins. KOBAYASHI et al (1992) and SATO et al (1995) also reported that the serum involved in the protective activity against E. rhusiopathiae infection in mice strongly reacted with the 64 and 43 kDa proteins.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they suggested that the antibody to the 64 kDa protein was important in the protection of mice against E. rhusiopathiae infection. GALÀ N and TIMONEY (1990) suggested that the antibody to the protective antigen expressed in Escherichia coli reacted strongly with the 66, 64 and 43 kDa proteins. KOBAYASHI et al (1992) and SATO et al (1995) also reported that the serum involved in the protective activity against E. rhusiopathiae infection in mice strongly reacted with the 64 and 43 kDa proteins.…”
Section: Western Blottingmentioning
confidence: 99%
“…From the results of our previous study (SATO et al, 1995), it was suggested that P64, which consists of 66 and 64 kDa proteins, exhibits a high degree of protective activity against Erysipelothrix rhusiopathiae infection in mice. GALÀ N and TIMONEY (1990) also reported that 66, 64 and 43 kDa structural proteins are important for protection against E. rhusiopathiae infection. GROSCHUP et al (1991) also reported that the 66-64 kDa protein exhibited in high degree of protective activity against E. rhusiopathiae infection in a mouse challenge test.…”
Section: Introductionmentioning
confidence: 96%
“…The anti-CF antiserum conferred crossprotection of mice when they were challenged with serovars 1a, 1b, 2, 5, 6, 8, 11, 12, 15, 16, 18, 21 and N strain (SAWADA and TAKAHASHI, 1987;SAWADA et al, 1987c). GALÁ TIMONEY (1990) and reported that 64 and 66 kDa proteins have strong protective activity against E. rhusiopathiae infection in mice. In our previous studies (KOBAYASHI et al, 1992;SATO et al, 1995), we found that the CF and the AE of E. rhusiopathiae strain Agata protected mice against the infection caused by several serotypes of E. rhusiopathiae and antisera involved in protective activity against E. rhusiopathiae infection in mice recognized the 64, 66 and 43 kDa proteins in both the CF and the AE.…”
Section: Western Blotting Using Anti-p64 and Anti-p43 Serummentioning
confidence: 99%
“…However, the yield of protective protein antigen from the CF and the AE of E. rhusiopathiae and the degree of protective activities of P64 and P43 in a mouse protection assay were not determined. GALÁ N and TIMONEY (1990) reported that structural proteins of 66, 64 and 43 kDa were important for protection against E. rhusiopathiae infection in mice. also reported that a 64-66 kDa protein exhibited a high degree of protective activity in a mouse challenge test.…”
Section: Introductionmentioning
confidence: 99%
“…GALÁ N and TIMONEY (1990) reported that the 66, 64 and 43 kDa bacterial structural proteins are important for the protection of mice against E. rhusiopathiae infection. GROSCHUP et al (1991) reported that the 66-64 kDa protein exhibited a high degree of protective activity in a mouse challenge test.…”
Section: Introductionmentioning
confidence: 99%